Surveillance of primary sclerosing cholangitis with ERC and brush cytology: risk factors for cholangiocarcinoma. (1st February 2017) - Boyd, Sonja; Mustonen, Harri; Tenca, Andrea; Jokelainen, Kalle; Arola, Johanna; Färkkilä, Martti A.
Abstract: Objective: Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease leading to bile duct strictures and fibrosis, and predisposing to cholangiocarcinoma (CCA). Biliary dysplasia is a known precursor of CCA. In our unit, PSC patients undergo regular surveillance with ERC and brush cytology (BC), and liver transplantation is an option in case with biliary dysplasia. We evaluated the risk factors for biliary dysplasia and CCA based on ERC imaging, BC and liver function tests. Patients and methods: Seven hundred and eighty-eight ERCs were performed with BC for 447 PSC patients. ERC images were evaluated using the modified Amsterdam score, neutrophilic inflammation was assessed in BC, and liver function tests were collected. Ploidy analysis with DNA flow cytometry was performed in cases with advanced PSC or previous suspicious BC/aneuploidy. The endpoint was either a benign disease course (follow-up for ≥2.4 years after the latest ERC), benign histology, biliary dysplasia or CCA. Results: Benign disease course was seen in 424/447 (including 23 cases with biliary dysplasia), and CCA in 17 (3.8%) patients. Gallbladder carcinoma/carcinoma in situ was diagnosed in three patients. Advanced ERC findings, male gender, suspicious BC, aneuploidy in flow cytometry, inflammation, and elevation of ALP, bilirubin, ALT, AST, GGT, CEA and CA19-9 represented significant risk factors for CCA in univariate analysis. Conclusions: PSC patients with advanced bile duct disease and elevated liver enzymes, CEA or CA19-9, inflammation or suspicious BC are most likely to develop CCA. These patients may benefit from surveillance with BC if early liver transplantation is possible.